2018
DOI: 10.1016/j.ijbiomac.2018.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different chemical modifications on the antibacterial activities of polysaccharides sequentially extracted from peony seed dreg

Abstract: The peony seed dreg polysaccharide (PSDPs) fractions and their modified derivatives were examined for their antibacterial potential. PSDPs along with their derivatives exhibited appreciable antibacterial activity against both Gram-positive (B. subtilis and S. aureus) as well as Gram-negative (E. coli and S. typhimurium) bacteria. Among the four polysaccharide fractions, HBSS possessed the greatest antibacterial activity with an inhibition zone of 13.6 mm against S. typhimurium, minimal inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Paeoniflorin, as a unique chemical substance in peony plants, showed strong antibacterial effects [ 41 ]. Additionally, the polysaccharide obtained from peony seed dregs showed antibacterial activity against both Gram-positive ( B. subtilis and S. aureus ) and Gram-negative ( E. coli and S. typhimurium ) bacteria [ 42 ]. There are abundant polyphenols in the seeds of wild peony plants [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Paeoniflorin, as a unique chemical substance in peony plants, showed strong antibacterial effects [ 41 ]. Additionally, the polysaccharide obtained from peony seed dregs showed antibacterial activity against both Gram-positive ( B. subtilis and S. aureus ) and Gram-negative ( E. coli and S. typhimurium ) bacteria [ 42 ]. There are abundant polyphenols in the seeds of wild peony plants [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Peony extract is a natural extract that is widely known for its antibacterial activity. According to previous studies, peony extracts have weak antibacterial and toxic properties (Li et al, 2018;Krzyściak et al, 2017). Therefore, we intended to produce a tissue control agent containing a peony extract by applying tissue control to the peony extract.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from that, both Lsbl-bk1 and Lsbl-bk2 levan products, as exoploysaccharides, have beneficial potency as an antibacterial agent. Previous studies have shown that exopolysachharides with antimicrobial activity could inhibit the growth of S. aureus, E. coli, and P. aeruginosa with an inhibition zone diameter about 15-20 mm [44,46] . It has also been assumed that exopolysaccharide levans can disrupt the bacterial cell wall integrity by blocking nutrients input [36,46] .…”
Section: Discussionmentioning
confidence: 99%